2006
DOI: 10.1002/ange.200600987
|View full text |Cite
|
Sign up to set email alerts
|

CO Fixation to Stable Acyclic and Cyclic Alkyl Amino Carbenes: Stable Amino Ketenes with a Small HOMO–LUMO Gap

Abstract: Fix gebunden: Anders als cyclische Diaminocarbene reagieren stabile Alkylaminocarbene mit CO zu stabilen Ketenen (Schema oben). Im Unterschied zu den acyclischen Derivaten können cyclische Aminoketene der destabilisierenden n‐π‐Donorfunktion des freien N‐Elektronenpaars nicht ausweichen, was zu einem Diradikalcharakter und ungewöhnlichen optischen (Schema unten und Photos von Kristallen) wie NMR‐spektroskopischen Eigenschaften führt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
71
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(84 citation statements)
references
References 53 publications
6
71
0
7
Order By: Relevance
“…Compared to the optimized structure of the free NHC, the dihedral angles of 2 are significantly diminished in both its d 6 and d 10 metal complexes, the calculated values ranging in between 0  4 and 0  7, respectively. Although a moderate decrease in dihedral angles is observed for 2 in its copper and silver compounds, the optimized geometry obtained for the gold complex stands clearly out from the rest by having a fully planar heterocyclic ring framework.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Compared to the optimized structure of the free NHC, the dihedral angles of 2 are significantly diminished in both its d 6 and d 10 metal complexes, the calculated values ranging in between 0  4 and 0  7, respectively. Although a moderate decrease in dihedral angles is observed for 2 in its copper and silver compounds, the optimized geometry obtained for the gold complex stands clearly out from the rest by having a fully planar heterocyclic ring framework.…”
mentioning
confidence: 85%
“…The metal-ligand bond strength increases down a group for d 0 complexes while for d 6 Of all the systems studied, the carbenes 3 and 5 form the strongest and weakest bonds with a given metal, respectively. The only exceptions are the d 0 metal complexes of 2 and 1.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Small cyclic unsaturated hydrocarbons such as c-C 3 H, c-C 3 H 2 , c-C 3 H 3 , and c-C 4 H 4 are of great interest for the chemistry of carbon-rich gas-phase environments [1][2][3][4][5][6] and have been the subject of numerous theoretical and experimental investigations. These cyclic molecules are believed to be vital intermediates in the chemical schemes leading to the formation of large carbon-containing molecules such as polycyclic aromatic hydrocarbons in combustion flames, the interstellar environment, and extraterrestrial atmospheres such as on a moon of Saturn, Titan.…”
Section: Introductionmentioning
confidence: 99%
“…2 In recent years, it has been shown that the backbones of NHCs can be significantly modified without diminishing their stability and examples of saturated 7 and acyclic 8 carbenes, and NHCs with four-, six-, and seven-membered rings have been reported; 9 the first example of a stable carbene which remarkably lacks π-donor heteroatoms has also been published. 10 In addition, there have been extensive efforts to isolate and characterize the isovalent p-block analogues of imidazol-2-ylidene, collectively known as the main group carbene analogues. These compounds have been successfully synthesized for many elements from Groups 13 to 16: 11 in each case, the main group centre is dicoordinate, electron rich (bears a lone pair of electrons), and formally anionic (Group 13), neutral (Group 14), cationic (Group 15), or dicationic (Group 16).…”
Section: Introductionmentioning
confidence: 99%